Participatory Approach to Develop Evidence-Based Clinical Ethics Guidelines for the Care of COVID-19 Patients: A Mixed Method Study From Nepal - Bhattarai, Suraj; Adhikari, Anurag; Rayamajhee, Binod; Dhungana, Jaya; Singh, Minu; Koirala, Sarun; Shakya, Dhana Ratna (Frontiers in Public Health, 2022)
During health emergencies such as COVID-19 pandemic, healthcare workers face numerous ethical challenges while catering to the needs of patients in healthcare settings. Although the data recapitulating high income country ethics frameworks are available, the challenges faced by clinicians in resource limited settings of low- and middle-income countries are not discussed widely due lack of the baseline data or evidence. Nepali healthcare system, which is chronically understaffed and underequipped, was severely affected by COVID-19 pandemic in its capacity to manage health services and resources to the needy patients, leading to ethical dilemma and challenges during clinical practice. This study aimed to develop a standard guideline that would address syndemic ethical dilemmas during clinical care of COVID-19 patients who are unable to afford standard-of-care. A mixed method study was conducted between February and June of 2021 in 12 government designated COVID-19 treatment hospitals of central Nepal. The draft guideline was discussed among the key stakeholders of pandemic response in Nepal. The major ethical dilemmas confronted by the study participants (50 healthcare professionals providing patient care of COVID-19 treatment hospitals) could be grouped into five major pillars of ethical clinical practice: rational allocation of medical resources, updated treatment protocols that guide clinical decisions, standard-of-care regardless of patient’s economic status, effective communication among stakeholders for prompt patient care, and external factors such as political and bureaucratic interference affecting ethical practice. This living clinical ethics guideline, which has been developed based on the local evidences and case stories of frontline responders, is expected to inform the policy makers as well as the decision makers positioned at the concerned government units. This ethics guidelines could be endorsed with revisions by the concerned regulatory authorities for the use during consequent waves of COVID-19 and other epidemics that may occur in the future. Other countries affected by the pandemic could conduct similar studies to explore ethical practices in the local clinical and public health context.